Safety of COVID-19 Vaccines among People with History of Allergy: A European Active Surveillance Study - Nicoletta Luxi; Francesco Ciccimarra; Chiara Bellitto; Monika Raethke; Florence van Hunsel; Thomas Lieber; Erik Mulder; Luca L’Abbate; Francisco Batel Marques; Fabiana Furci; Andreea Farcas; Janneke Giele-Eshuis; et al. (Vaccines)
Background: Conventional vaccines rarely cause severe allergic reactions. However, the rapid development and approval of COVID-19 vaccines left limited initial data on their adverse reactions, particularly in individuals with a history of allergy. The aim of this study was to assess and compare the safety profile of different doses and brands of COVID-19 vaccines in subjects with a history of allergy vs. those without a history of allergy. Methods: From February 2021 to February 2023, a web-based prospective study gathered vaccinee-reported outcomes using electronic questionnaires across eleven European countries. Baseline and up to six follow-up questionnaires captured data on vaccinee demographics, as well as both solicited and unsolicited adverse reactions. Results: Overall, 3476 vaccinees with a history of allergy were matched with 13,872 vaccinees from the general population at the first vaccination cycle and were included in the analysis. A total of 825 vaccinees with a history of allergy who had received a booster dose, matched to 3297 vaccinees from the general population, were included in the analysis. Higher rates of ADRs occurred after the first vaccination cycle compared to after the booster dose (64–91% vs. 56–79%). However, most reported ADRs were solicited and not serious, and no case of anaphylaxis was reported. Women and vaccinees with a history of allergy reported ADRs more frequently than men and the matched controls, respectively. Compared to other COVID-19 vaccines, a higher proportion of vaccinees experiencing at least one ADR following their first vaccination cycle was observed with Comirnaty and Vaxzevria. Statistically significant differences were observed among the study cohorts for median TTO after the second dose, and for median TTR following the first vaccination cycle and booster dose (p < 0.001). Conclusions: Typically, any drug or vaccine use carries a risk of severe allergic reactions, yet the benefits of vaccination generally outweigh these potential risks, as shown with the COVID-19 vaccines.